THE EFFECT OF ACTIVITY, PROFITABILITY, LIQUIDITY, AND SALES GROWTH ON THE FINANCIAL DISTRESS OF PROPERTY AND REAL ESTATE COMPANIES - Herni Kurniawati; Sriwati Sriwati; Verawati Verawati (Graduate Program of Universitas Tarumanagara, 2026)
The property crisis in China brings various complex impacts for Indonesia. From the reduction of foreign investment, the decline in commodity demand, to financial market instability, all of this requires Indonesia to be prepared and adaptive in facing changes. The government and business actors need to take strategic steps to mitigate the negative impacts and seize the opportunities that arise amidst these challenges. Therefore, initial steps are needed to detect financial distress in Indonesian property and real estate companies using financial ratios. Financial ratios are indicators of financial performance that can predict companies experiencing a decline in financial performance, which tend to face financial distress. The objective of this research is to empirically examine how activity ratio, profitability ratio, liquidity ratio, and sales growth ratio can affect the financial distress condition of companies in the property and real estate sector for the period 2019-2024The utilized research design is descriptive, incorporating a quantitative method through panel data regression analysis. The findings indicate that the activity and profitability ratios negatively influence financial distress, whereas the liquidity ratio positively impacts financial distress for property and real estate firms. Additionally, the sales growth ratio does not adversely affect the financial distress situation of property and real estate firms.